Saranukrom watthanatham Phak Tai, Pho. So. 2529. - Mahawitthayalai Sinakharinwirot Songkhla. Sathaban Thaksinkhadisuksa ([Songkhla, Thailand] : Sathaban Thaksinkhadisuksa, Mahawitthayalai Sinakharinwirot Songkhla, 1986)
Encyclopedia of southern Thai culture.
In Thai.
"Munnithi Toyota sanapsanun kanchattham lae kanphim."
Keywords: Thailand, Southern -- Encyclopedias